Enhancing nano zero-valent iron (nZVI) performance for Cr(VI) removal through zeolite imidazole framework-8 (ZIF-8) coating - Xiaobin Zhou; Chenyu Zhou; Min Huang; Yingxue Wang; Mengxin Zhao; Yanan Zhang; Yinming Fan; Yinian Zhu; Zongqiang Zhu (Water Cycle, 2025)
Nano zero-valent iron (nZVI) has garnered significant attention as an excellent environmental remediation material for Cr(VI) adsorption. However, its practical utilization is significantly impeded by inherent limitations, notably its propensity for aggregation and susceptibility to oxidation. This study proposed an innovative approach that using zeolite imidazole framework-8 (ZIF-8) as a cladding material for encapsulating nZVI particles. This encapsulation served to safeguard nZVI from oxidation and agglomeration. Furthermore, the ZIF-8 coating possessed suitable pore channels, allowing the migration of Cr(VI) ions towards the nZVI's surface, thereby enabling efficient reduction. The ZIF-8-coated nZVI composite (ZIF-8@nZVI) achieved a remarkable Cr(VI) removal efficiency of 98.43% under the optimized conditions. After 10 days of exposure in the aqueous solution, the efficiency remained above 84%. The uptake of Cr(VI) by ZIF-8@nZVI proceeded via a chemisorption pathway, inherently spontaneous and endothermic in character. The mechanism analysis indicated that ZIF-8 and nZVI exhibited synergistic enhancement effect on Cr(VI) removal. The protonated nitrogen groups within ZIF-8 facilitated the swift diffusion of negatively charged Cr(VI) ions to the surface of ZIF-8@nZVI. Once adsorbed, Cr(VI) was directly reduced to Cr(III) by Fe0, which in turn underwent oxidation to Fe(II)/Fe(III). Notably, Fe(II) indirectly reduced Cr(VI) to Cr(III), while itself being oxidized to Fe(III). Consequently, the resulting Cr(III) ions co-precipitated with Fe(III), forming hydroxide complexes that were eliminated from the aqueous environment. Overall, this research demonstrated the practicability of employing ZIF-8 as a coating material to develop highly efficient nZVI-based adsorbents and highlighted the potential of ZIF-8@nZVI in addressing Cr(VI) contamination challenges.